Melacak Ruang Kajian Pemerintahan Dalam Ilmu Politik: Sebuah Riset Awal - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRAK The label of 'science' (ilmu) (in Indonesia case), which then followed by certain subjects such as Political Science (Ilmu Politik), Governmental `Science' (Ilmu Pemerintahan), and International Relations 'Science' (Ilmu Hubungan Internasional), is popularized, on a regular basis, by its institutional establishment than by its theory and methodology literatures. This article is trying to discuss the definition of governmental 'science' (Ilmu Pemerintahan). Albeit there is no reference which relatively rigid and consently approved on its description, this label of governmental 'science' is remain recognized as its function as a department's name (jurusan) in most of the university in Indonesia. The discussion is begin by preliminary clarifications on what is government (pemerintahan), governmental 'science' (ilmu pemerintahan), and government studies. This topic will open the assessment by elaborate the term of government and politics through observe its function in selected literatures. The discussion of this topic will be supported by a review on the reason behind the establishment of urusan Pemerintahan (departement of government), jurusan Ilmu Politik (departement of political science), and jurusan Ilmu Pemerintahan (departement of governmental `science'), as different institution with different discourses. The topic will be concluded by a proposal to initiate government studies (studi pemerintahan), as an alternative of governmental 'science' (Ilmu Pemerintahan).